Spremljanje tujerodnih ambrozijskih podlubnikov - Pajek, Luka (Acta silvae et ligni, 2020)
Ambrosia bark beetles have been identified as one of the most invasive non-native organisms. The species Xylosandrus germanus, which was first recorded in Slovenia in the year 2000, is highly adaptable to novel environments. The aim of the current study was to confirm the presence and determine the actual population size of X. germanus in the Šentvid forest district (within the Škofljica local unit of the Slovenia Forest Service). Monitoring was conducted using home-made traps from plastic bottles. The traps were set in three different forest stands, namely 4 traps with different attractants (i.e. ethanol, denatured ethanol, a blend of ethanol and %-pinene and unbaited (control) trap) were set in each stand. Ethylene glycol was used as a preservative. The traps, which were monitored over an eight-week period, i.e. between 26th April 2017 and 20th June 2017, were emptied on a weekly basis, and the trap captures were subsequently determined in the Laboratory for Ecological Research - Entomology at the Department of Forestry and Renewable Forest Resources at the Biotechnical Faculty. A total of 11,460 captured X. germanus individuals comprised 90.09 % of all the collected beetle specimens, or 95.30 % of all the captured bark beetle specimens. Such a large catch indicates that the population size of X. germanus in the research area is large. In addition to X. germanus, we confirmed the presence of another non-native ambrosia bark beetle, namely Gnathotrichus materiarius. Our results show that there are no significant differences in the efficiency of attracting X. germanus between the tested attractants. A high proportion of X. germanus specimens in the catch undoubtedly confirms that home-made traps from disposable plastic bottles represent a viable monitoring tool for the surveillance of non-native ambrosia bark beetle populations.
Keywords: ambrosia bark beetles; ambrozijski podlubniki; attractants; forest; gozdovi; invasive alien species; invazivne tujerodne vrste; pasti; Slovenia; Slovenija; spremljanje; traps; vabe; Xylosandrus germanus